Prohibition of Discrimination on Grounds of Disability in Slovak, Czech, and Polish Labor Law - Dolobáč, Marcel; Kundrát, Ivan (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
The article examines the prohibition of discrimination on the grounds of disability in Slovak, Czech, and Polish labor law, with a particular focus on the definition of disability and its alignment with European Union law. While Slovakia and Poland emphasize a formalized recognition of disability through administrative decisions, Czech legislation provides a more material definition consistent with the case-law of the Court of Justice of the European Union. The comparative analysis highlights differences in legal frameworks and the challenges of harmonizing national concepts with the EU’s substantive approach. The study underscores that effective protection requires not only legislative transposition of Directive 2000/78/EC but also its practical implementation, aiming to ensure both formal and substantive equality in employment for persons with disabilities.